THE PHONOSTYLISTICS OF ENGLISH SPEECH: CLASSIFICATION AND CHARACTERISTICS - Adila Tadjibaeva (Western European Studies, 2024)
This article investigates the various types of speech in the English language and their phonostylistic classifications, offering a comprehensive analysis of how phonetic variations are influenced by context, purpose, and audience. Phonostylistics, the study of the relationship between phonetic features and speech styles, provides a framework for understanding the distinct characteristics of different speech types. The analysis covers formal speech, informal speech, public speaking, conversational speech, and oral presentations, each exhibiting unique phonetic and stylistic traits. By examining these speech types through a phonostylistic lens, the article aims to enhance the understanding of speech variation, contributing valuable insights to the fields of linguistics, communication studies, and phonetics. This exploration is crucial for linguists, educators, speech therapists, and anyone interested in the subtleties of spoken English
Keywords: Phonostylistics speech types; English language; formal speech